Pengaruh PDB, Kurs, dan Inflasi Terhadap Impor Produk Telekomunikasi di Indonesia - Assifadya, Wirdajati; Wardhana , Ali (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2022)
This research was conducted to determine simultaneously the influence of GDP, exchange rates, and inflation and which factors were the most dominant in influencing the import of telecommunications products in Indonesia. The data used in this study are secondary time-series data for 18 years, starting from 2002 to 2019. Data were obtained from the Central Statistics Agency, Bank Indonesia, and the World Bank. The data analysis tool uses OLS (Ordinary Least Square) and is estimated using Eviews 9 software. The results showed that the variable GDP had a significant effect on imports of telecommunications products in Indonesia. The exchange rate and inflation variables do not significantly influence the import of telecommunications products. The coefficient of determination is 0.811884, which means that the independent variable GDP, exchange rate, and inflation affect 81.184% of the dependent variable of importing Indonesian telecommunications products.